FAMILY HOLDING IN RURAL ACTIVITY: A TAX APPLICABILITY THAT BRINGS RESULTS? - Alesi, Jean; Wantroba, Elaine (Revista e-TECH: Tecnologias para Competitividade Industrial - ISSN - 1983-1838, 2025)
Agribusiness in Brazil is one of the main economic activities, contributing significantly to the country's Gross Domestic Product (GDP). According to CEPEA/CNA estimates (CEPEA, 2024), agribusiness' share of GDP is expected to be around 23.80 per cent, an increase compared to 23.57 per cent in 2023. The agricultural sector is experiencing remarkable growth, with an increase of 0.23 per cent in 2024, underpinned by an emphasis on sustainability, according to data from Esalq/USP in partnership with CEPEA (2024). The harvest of various products, including soya, corn, wheat, coffee, cocoa, potatoes and sugar cane, has reached record levels in Brazil, even amid falling prices for primary products and agricultural inputs. This trend reflects efficient management of the sector. An important strategy for managing family agribusiness is the creation of a rural family holding company. As a result of the research, it is important to emphasise that the rural family holding company can be a valuable strategy for asset and succession management in rural properties, especially with regard to tax issues.